Co-existence of NDM-1 and OXA-48 genes in Carbapenem Resistant Klebsiella pneumoniae clinical isolates in Kafrelsheikh, Egypt - El-Domany, Ramadan Ahmed; El-Banna, Tarek; Sonbol, Fatma; Abu-Sayedahmed, Samar Hamed (African health sciences, 2021)
Background: The noteworthy spread of carbapenem-resistant K. pneumoniae (CR-KP) isolates represents a significant safety threat. Objective: Determination of the carbapenemase genes incidence among CR-KP clinical isolates in Kafrelsheikh, Egypt. Methods: A total of 230 K. pneumoniae isolates were recovered from four hospitals in Kafrelsheikh, Egypt. Susceptibility testing was conducted using Kirby-Bauer method and automated-Vitek2 system. CR-KP isolates were tested using modified Hodge test (MHT) and combined disk synergy test. PCR and DNA sequencing were conducted for CR-KP isolates to recognize the included carbapenemase-genes. Results: Out of 230 K. pneumoniae isolates, 50 isolates presented resistance to carbapenem (meropenem). All 50 CR-KP isolates were multidrug-resistant (MDR). Genes like blaNDM-1 and blaOXA-48 were the only detected genes among CR-KP with an incidence of 70.0% and 52.0%, respectively. Up to 74.0% of the tested isolates carried at least one of the two recorded genes, among them 48.0% co-harbored both blaNDM-1 and blaOXA-48 genes. The accession-numbers of sequenced blaNDM-1 and blaOXA-48 genes were MG594615 and MG594616, respectively. Conclusion: This study reported a high incidence of MDR profile with the emergence of blaNDM-1 and blaOXA-48 genes co-existence in CR-KP isolates in Kafrelsheikh, Egypt. Hence, more restrictions should be applied against the spread of such serious pathogens.